ANALISIS KESALAHAN PENGGUNAAN ADJEKTIVA KUALITATIF BAHASA PRANCIS: STUDI KASUS PADA MAHASISWA SEMESTER V TAHUN AKADEMIK 2010/2011 PROGRAM STUDI BAHASA DAN SASTRA PRANCIS UNIVERSITAS BRAWIJAYA - JOEL, CHRISTIAN EKAPUTRA (Jurnal Ilmiah Mahasiswa FIB, 2013)
This study aimed to describe the most dominant language errors made bystudents on the using of qualitative adjectives in French. The method used is descriptivequalitative methods and data sources are the results of tests of french qualitativeadjective . The sample in this study is the 5th semester students of Academic Year2010/2011 Study Program of French Language and Literature, Faculty of Humanities,University of Brawijaya, amounting to 37 students.Techniques of data collection use the documentation, bibliographies and testinstrument. In order to complete the elements of the validity, this study uses the expertsjudgment technique. The instrument tested is the short answer questions that consist of2 questions , the determination of the location of the test that consist of 3 questions andthe randomthat consist of 2 questions. To analyze the results of tests conducted therecap of each test question answers in the form of a table based on the results ofcalculation formula, and then proceed with the identification and classification of faults,fault grading and description of error.Results of data analysis tests given to students on the using of qualitativeadjectives in French suggests that the types of errors made by the students comprise 40taxonomic categories of linguistic errors (70%) and 17 surface strategy taxonomy errors(30%). Thus it can be said that the most dominant language errors made by students islinguistic category taxonomy mistake.  Keywords: language error, qualitative adjectives